Metaphor from the ground up understanding figurative language in context - Strack, Daniel C., 1967- (Lexington Books, an imprint of The Rowman & Littlefield Publishin Group, Inc., 2019)
Cross-referencing neurobiological knowledge with the invariance hypothesis, relevance theory, and frame semantics, Metaphor from the Ground Up: Understanding Figurative Language in Context unifies metaphor theory, fundamentally rethinks "context," and moves linguistics into the twenty-first century.